Worst Pattern of Perineural Invasion Redefines the Spatial Localization of Nerves in Oral Squamous Cell Carcinoma - Fu, Yong; Zhang, Xinwen; Ding, Zhuang; Zhu, Nisha; Song, Yuxian; Zhang, Xiaoxin; Jing, Yue; Yu, Yijun; Huang, Xiaofeng; Zhang, Lei; Hu, Qingang; Ni, Yanhong; et al. (Frontiers in Oncology, 2021)
As a key histopathological characteristic of tumor invasion, perineural invasion (PNI) assists tumor dissemination, whereas the current definition of PNI by dichotomy is not accurate and the prognostic value of PNI has not reached consensus. To define PNI status in each patient when mixed types of PNI occurred simultaneously, we here further subclassified the traditional PNI in 183 patients with oral squamous cell carcinoma (OSCC). The spatial localization of nerves in OSCC microenvironment was thoroughly evaluated and successfully concluded into four types of PNI: 0, tumor cells away from nerves; 1, tumor cells encircling nerves less than 33%; 2, tumor cells encircling nerves at least 33%; and 3, tumor cells infiltrating into nerve sheathes. Sequentially, patients were stratified by single and mixed types of PNI. Traditionally, types 0 and 1 were defined as PNI−, while types 2 and 3 were PNI+, which predicted shorter survival time. When multiple types of PNI existed within one tumor, patients with higher score of PNI types tended to have a relatively worse prognosis. Therefore, to define the status of PNI more precisely, the new variable worst pattern of PNI (WPNI) was proposed, which was taken as the highest score of PNI types present in each patient no matter how focal. Results showed that patients with WPNI 1 had longest survival time, and WPNI 2 correlated with better overall survival (p = 0.02), local-regional recurrence-free survival (p = 0.03), and distant metastasis-free survival (p = 0.046) than WPNI 3. Multivariate Cox analysis confirmed that only WPNI 3 could independently predict patients’ prognosis, which could be explained by a more damaged immune response in WPNI 3 patients with less CD3+CD8+ T cells and CD19+ B cells. Conclusively, WPNI by trichotomy provide more meticulous and precise pathological information for tumor-nerve interactions in OSCC patients.